Nylon fabric and preparation method thereof

By carboxymethylation modification and emulsion polymerization technology on nylon fabrics, silicone flame retardant is formed, which solves the problems of nylon fabrics melting and dropping and flame retardant performance during combustion, and achieves efficient flame retardant effects and Target to reduce production costs.

CN118910893BActive Publication Date: 2024-12-13WUJIANG LANTIAN TEXTILE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411409354.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-13
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

Existing nylon fabrics are prone to melt droplets when burned, have poor flame retardant performance, and are high in production costs, making it difficult to achieve large-scale production.

Method used

After soaking the nylon fabric in a sodium carbonate solution and heating it, carboxymethylation modification is performed, and carboxylic groups are introduced under the action of ethylene glycol and tartaric acid, followed by impregnation in the solution of parabenzoic acid and phosphate amide to form β -hydroxyester bond; then a mixture of γ-glycidyl etheroxypropyl trimethoxysilane and aminopropyl triethoxysilane was added to the solution of tetramethylphosphorus hydroxide and sodium dodecyl sulfate to carry out an emulsion Polymerization forms silicone flame retardant, increasing the flame retardant properties of nylon fabrics.

Benefits of technology

It has achieved good flame retardant effect of nylon fabrics, with an extreme oxygen index of 29.4%, a weight gain rate of 18.24%, and no melt drops, which reduces production costs and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118910893B_ABST
    Figure CN118910893B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of textile technology, and specifically relates to a nylon fabric and a preparation method thereof. The present invention adopts an emulsion polymerization method to polymerize γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane on the surface of a nylon fabric to form an organosilicon flame retardant. When burning, the flame retardant will form an oxygen-insulating and heat-insulating protective layer on the surface of the nylon fabric, effectively preventing the nylon fabric from continuing to burn, and has a good flame retardant effect. The limiting oxygen index of the nylon fabric provided by the present invention can reach 29.4±0.1%, the weight gain rate can reach 18.24%, and no molten droplets will fall during burning, and it has a good flame retardant effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of textiles, and in particular relates to a nylon fabric and a preparation method thereof. Background Art

[0002] Nylon fiber is a thermoplastic resin containing repeated amide groups on the main chain of the molecule. It has the advantages of light weight, easy to wash and dry, not afraid of mold and mildew, high strength and acid and alkali resistance. It is widely used in the textile field. With the improvement of people's living standards, the requirements for textiles are getting higher and higher. Since the melting point of nylon fiber is lower than the ignition point, it is very easy to shrink during the combustion process and produce a large number of molten droplets, which may burn the skin and cause safety hazards. Therefore, it is urgent to improve the flame retardant properties of nylon fabrics.

[0003] There are three common methods for nylon flame retardancy: flame retardant blending and post-finishing. Flame retardant blending is to mix the flame retardant with the nylon fiber raw material and then melt-spin. It can only be used in the textile preparation process and cannot be used for formed nylon fabrics. The post-finishing method has the advantages of simple process and easy operation, but there are no active groups in the nylon fiber structure, so it needs to be irradiated to activate the fabric and then graft the flame retardant functional groups onto the nylon fiber surface. The production cost is high, the monomers available are limited, and it is difficult to achieve large-scale production.

[0004] For example, a Chinese patent application document with publication number CN103866563A discloses a flame retardant grafting modification method for nylon 66 fabric, in which a microwave method is used for grafting reaction, and allylthiourea is used as a grafting monomer. The combustion performance of the grafted nylon 66 fabric is significantly improved, and the nylon fabric is modified by microwave irradiation. A Chinese patent application document with publication number CN116200027A discloses a flame-retardant nylon and a preparation method thereof, wherein the flame-retardant nylon comprises: nylon; a phosphorus-nitrogen-silicon cross-linked polymer, wherein the phosphorus-nitrogen-silicon cross-linked polymer is a reaction product of a phosphorus-nitrogen-containing diacid monomer and a silicon-containing epoxy monomer under the action of a catalyst, and comprises a β-hydroxy ester bond formed by an ester exchange reaction between an epoxy group and a carboxyl group; and a product of a melt-kneading reaction between the phosphorus-nitrogen-silicon cross-linked polymer and the nylon part, wherein the product comprises an exchange product between the β-hydroxy ester bond and an amide bond in the nylon, and a chain extension product of the reaction between an amino group and a carboxyl group in the nylon, and a hydroxyl group in the phosphorus-nitrogen-silicon cross-linked polymer and an epoxy group. Summary of the invention

[0005] In order to solve the technical problems existing in the related art such as molten droplet dripping, poor flame retardant effect, high production cost, etc., the purpose of the present invention is to provide a nylon fabric and a preparation method thereof.

[0006] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:

[0007] A method for preparing nylon fabric comprises the following steps:

[0008] S1. The nylon fabric was immersed in a sodium carbonate solution, heated to boiling and boiled for 1-2h, cooled, removed the nylon fabric, washed with water to obtain a pretreated nylon fabric;

[0009] S2. The pretreated nylon fabric obtained in step S1 was immersed in an aqueous solution of ethylene glycol, tartaric acid was added, stirred at a speed of 1200-1400rpm for 0.5-1h, the nylon fabric was removed, washed with water to neutrality after drying, and dried at room temperature to obtain a modified nylon fabric I;

[0010] S3. The modified nylon fabric I obtained in step S2 is immersed in a mixed solution of p-hydroxybenzoic acid and phosphate amide in ethanol, heated to 50-60 ° C, the immersion time is 1-1.5h, the nylon fabric is removed, and washed with water to obtain a modified nylon fabric II;

[0011] S4. Soak the modified nylon fabric II obtained in step S3 in an aqueous solution of tetramethylphosphonium hydroxide and sodium dodecyl sulfate, heat to 40-50°C, dropwise add a mixture of γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane, stir for 3.5-4h, take out the nylon fabric, wash with clean water, and dry to obtain.

[0012] The heating and boiling process of nylon fabric in alkaline solution can convert the terminal groups of the macromolecular chain of nylon fiber fabric into reducing terminal groups, creating conditions for the subsequent reaction. Ethylene glycol and tartaric acid are used to modify nylon fabric by carboxylmethylation, and carboxyl groups are introduced into the macromolecular chain of nylon fiber, laying the foundation for the subsequent connection of flame retardants.

[0013] The invention soaks the carboxymethyl modified nylon fabric in an ethanol solution of p-hydroxybenzoic acid and phosphate amide, and the hydroxyl groups in the p-hydroxybenzoic acid and the amino groups in the phosphate amide react with the carboxyl groups on the molecular surfaces of the carboxymethyl modified nylon fabric, so that the p-hydroxybenzoic acid and the phosphate amide are grafted onto the surface of the nylon fabric, and benzene rings and organic phosphorus are introduced, thereby greatly improving the flame retardant performance of the nylon fabric.

[0014] The present invention adopts the method of emulsion polymerization to polymerize γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane on the surface of nylon fabric to form an organosilicon flame retardant. The main chain of the molecule contains a large number of silicon-oxygen bonds. When the nylon fabric burns, a layer of silicon-oxygen bonds and / or silicon-carbon bonds with excellent thermal stability and oxidation stability will be formed on the surface of the nylon fabric to form an inorganic oxygen-insulating protective layer, which prevents the combustion from proceeding and inhibits the thermal decomposition of nylon polymers. The branched structure of the flame retardant helps to form a cross-linked structure in the solid phase residue, thereby improving the thermal stability of the nylon fabric. In addition, the amino groups contained in the polymer molecules formed by γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane can also react with the carboxyl groups on the modified nylon fabric molecules, further enhancing the binding force between the flame retardant and the nylon molecules, which is beneficial to improving the flame retardant properties of the nylon fabric.

[0015] Furthermore, in step S1 of the method for preparing the nylon fabric, the concentration of the sodium carbonate solution is 0.06-0.08 mol / L, and the pH value is 8.5-9.

[0016] Furthermore, in step S2 of the method for preparing the nylon fabric, the mass percentage of ethylene glycol is 20-25%.

[0017] Furthermore, in step S2 of the method for preparing the nylon fabric, the amount of tartaric acid used is 15-17% of the mass of the nylon fabric.

[0018] Furthermore, in the preparation method of the nylon fabric, the immersion temperature in step S2 is 75-80°C.

[0019] Furthermore, in step S3 of the method for preparing the nylon fabric, the concentration of p-hydroxybenzoic acid is 0.5-0.7 mol / L, and the concentration of phosphate amide is 0.15-0.2 mol / L.

[0020] Furthermore, in step S4 of the method for preparing the nylon fabric, the concentration of tetramethylphosphonium hydroxide is 0.02-0.03 mol / L, and the concentration of sodium dodecyl sulfate is 0.03-0.04 mol / L.

[0021] Furthermore, in step S4 of the method for preparing the nylon fabric, the dripping speed of the mixture of γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane is 2.2-2.6 m / s. 3 / h.

[0022] Furthermore, in step S4 of the method for preparing the nylon fabric, the mixing mass ratio of γ-glycidyloxypropyltrimethoxysilane to aminopropyltriethoxysilane is 2-5:9-13.

[0023] The invention also provides a nylon fabric prepared by using the preparation method of the nylon fabric.

[0024] Compared with the prior art, the nylon fabric and the preparation method thereof provided by the present invention have the following technical advantages:

[0025] (1) The limiting oxygen index of the nylon fabric provided by the present invention can reach 29.4±0.1%, the weight gain rate can reach 18.24%, and no molten droplets fall during combustion, thus having a good flame retardant effect;

[0026] (2) The present invention grafts flame retardant molecules onto the molecular structure of nylon fabrics through emulsion polymerization. When burning, the flame retardant will form an oxygen-insulating and heat-insulating protective layer on the surface of the nylon fabric, effectively preventing the nylon fabric from continuing to burn;

[0027] (3) The nylon fabric provided by the present invention can be grafted with flame retardant molecules without radiation, which effectively reduces the production cost and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is the heat release rate curve of nylon fabric;

[0029] Figure 2 is the combustion heat curve of nylon fabric;

[0030] Figure 3 It is the molecular structure formula of phosphate ester amide. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. Those skilled in the art can make various modifications based on the basic idea of ​​the present invention, but as long as they do not deviate from the basic idea of ​​the present invention, they are all within the scope of the present invention.

[0032] The phosphate ester amide used in this specific embodiment was purchased from Changzhou Jianmao Chemical Co., Ltd., and its molecular structure is shown in Figure 3 .

[0033] Embodiment 1, a kind of preparation method of nylon fabric

[0034] The preparation method of the nylon fabric comprises the following steps:

[0035] S1. The nylon fabric was immersed in a sodium carbonate solution having a concentration of 0.06mol / L and a pH value of 9, heated to boiling and boiled for 1h, cooled, the nylon fabric was removed, and washed with water to obtain a pretreated nylon fabric;

[0036] S2. The pretreated nylon fabric obtained in step S1 was immersed in a 20% by mass aqueous solution of ethylene glycol at 75°C, tartaric acid was added, the amount of tartaric acid was 15% by mass of the nylon fabric, and stirred at 1200rpm for 1h. The nylon fabric was taken out, washed with clean water until neutral after drying, and dried at room temperature to obtain a modified nylon fabric I;

[0037] S3. The modified nylon fabric I obtained in step S2 is immersed in an ethanol mixed solution of p-hydroxybenzoic acid and phosphate amide, wherein the concentration of p-hydroxybenzoic acid is 0.5 mol / L and the concentration of phosphate amide is 0.15 mol / L, heated to 50° C., and the immersion time is 1 h. The nylon fabric is taken out and washed with water to obtain a modified nylon fabric II;

[0038] S4. The modified nylon fabric II obtained in step S3 was immersed in an aqueous solution of tetramethylphosphonium hydroxide and sodium dodecyl sulfate, the concentration of tetramethylphosphonium hydroxide was 0.02 mol / L, the concentration of sodium dodecyl sulfate was 0.04 mol / L, the temperature was raised to 40°C, and the temperature was 2.2 m 3 / h, add a mixture of γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane in a mass ratio of 2:9, stir for 3.5h, take out the nylon fabric, wash it with clean water, and dry it to obtain the product.

[0039] Embodiment 2, a method for preparing nylon fabric

[0040] The preparation method of the nylon fabric comprises the following steps:

[0041] S1. The nylon fabric was immersed in a sodium carbonate solution having a concentration of 0.08mol / L and a pH value of 8.5, heated to boiling and boiled for 2h, cooled, the nylon fabric was removed, and washed with water to obtain a pretreated nylon fabric;

[0042] S2. The pretreated nylon fabric obtained in step S1 was immersed in a 25% by mass aqueous solution of ethylene glycol at 80°C, tartaric acid was added, the amount of tartaric acid was 17% by mass of the nylon fabric, and stirred at 1400rpm for 0.5h. The nylon fabric was taken out, washed with clean water until neutral after drying, and dried at room temperature to obtain a modified nylon fabric I;

[0043] S3. The modified nylon fabric I obtained in step S2 is immersed in an ethanol mixed solution of p-hydroxybenzoic acid and phosphate amide, wherein the concentration of p-hydroxybenzoic acid is 0.7 mol / L and the concentration of phosphate amide is 0.2 mol / L, heated to 60° C., and the immersion time is 1.5 h. The nylon fabric is taken out and washed with water to obtain a modified nylon fabric II;

[0044] S4. The modified nylon fabric II obtained in step S3 was immersed in an aqueous solution of tetramethylphosphonium hydroxide and sodium dodecyl sulfate, the concentration of tetramethylphosphonium hydroxide was 0.03 mol / L, the concentration of sodium dodecyl sulfate was 0.03 mol / L, the temperature was raised to 50°C, and the temperature was 2.6 m 3 A mixture of γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane is added dropwise at a rate of / h, the mixing mass ratio of γ-glycidyloxypropyltrimethoxysilane to aminopropyltriethoxysilane is 5:13, and the mixture is stirred for 4h. The nylon fabric is taken out, washed with clean water, and dried to obtain the product.

[0045] Embodiment 3, a method for preparing nylon fabric

[0046] The preparation method of the nylon fabric comprises the following steps:

[0047] S1. The nylon fabric was immersed in a sodium carbonate solution having a concentration of 0.07mol / L and a pH value of 8.8, heated to boiling and boiled for 1.5h, cooled, the nylon fabric was removed, and washed with water to obtain a pretreated nylon fabric;

[0048] S2. The pretreated nylon fabric obtained in step S1 was immersed in a 23% by mass aqueous solution of ethylene glycol at 79°C, tartaric acid was added, the amount of tartaric acid was 16% by mass of the nylon fabric, and stirred at 1300rpm for 0.8h. The nylon fabric was taken out, dried and washed with clean water until neutral, and dried at room temperature to obtain a modified nylon fabric I;

[0049] S3. The modified nylon fabric I obtained in step S2 is immersed in an ethanol mixed solution of p-hydroxybenzoic acid and phosphate amide, wherein the concentration of p-hydroxybenzoic acid is 0.6 mol / L and the concentration of phosphate amide is 0.18 mol / L, heated to 57° C., and the immersion time is 1.2 h. The nylon fabric is taken out and washed with water to obtain a modified nylon fabric II;

[0050] S4. The modified nylon fabric II obtained in step S3 was immersed in an aqueous solution of tetramethylphosphonium hydroxide and sodium dodecyl sulfate, the concentration of tetramethylphosphonium hydroxide was 0.027 mol / L, the concentration of sodium dodecyl sulfate was 0.035 mol / L, the temperature was raised to 46°C, and the temperature was 2.4 m 3 / h, add a mixture of γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane in a mass ratio of 4:11, stir for 3.7h, take out the nylon fabric, wash it with clean water, and dry it to obtain the product.

[0051] Comparative Example 1

[0052] The preparation method of the nylon fabric described in this comparative example is similar to that of Example 3. Step S4 in this comparative example is specifically as follows: soaking the modified nylon fabric II obtained in step S3 in an aqueous solution of tetramethylphosphonium hydroxide and sodium dodecyl sulfate, wherein the concentration of tetramethylphosphonium hydroxide is 0.027 mol / L and the concentration of sodium dodecyl sulfate is 0.035 mol / L, heating to 46°C, and heating at 2.4 m 3 Add γ-glycidyloxypropyltrimethoxysilane dropwise at a rate of / h, stir for 3.7h, take out the nylon fabric, wash it with clean water, and dry it to obtain the product.

[0053] That is, the difference between this comparative example and Example 3 is that in this comparative example, an equal amount of γ-glycidyloxypropyltrimethoxysilane is used instead of aminopropyltriethoxysilane.

[0054] Comparative Example 2

[0055] The preparation method of the nylon fabric described in this comparative example is similar to that of Example 3. Step S4 in this comparative example is specifically as follows: soaking the modified nylon fabric II obtained in step S3 in an aqueous solution of tetramethylphosphonium hydroxide and sodium dodecyl sulfate, wherein the concentration of tetramethylphosphonium hydroxide is 0.027 mol / L and the concentration of sodium dodecyl sulfate is 0.035 mol / L, heating to 46°C, and heating at 2.4 m 3 Add aminopropyltriethoxysilane dropwise at a rate of / h, stir for 3.7h, take out the nylon fabric, wash it with clean water, and dry it to obtain the product.

[0056] That is, the difference between this comparative example and Example 3 is that in this comparative example, an equal amount of aminopropyltriethoxysilane is used instead of γ-glycidyloxypropyltrimethoxysilane.

[0057] Comparative Example 3

[0058] The preparation method of the nylon fabric described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that the mixing mass ratio of γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane described in step S4 of this comparative example is 11:4.

[0059] Comparative Example 4

[0060] The preparation method of the nylon fabric in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that the dripping speed of the mixture of γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane in step S4 in this comparative example is 3.9 m / s. 3 / h.

[0061] Comparative Example 5

[0062] The preparation method of the nylon fabric in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that the nylon fabric in this comparative example is not subjected to carboxylation modification, that is, the preparation method of the nylon fabric in this comparative example does not perform the operation in step S2.

[0063] Test Example 1: Combustion Performance Test

[0064] Test samples: Nylon fabrics were prepared in Examples 1 to 3 and Comparative Examples 1 to 5; blank samples were prepared using original nylon fabric.

[0065] Test method: According to GB / T 5454-2008 “Textile combustion performance test oxygen index method”, the limiting oxygen index (LOI) of the fabric is measured using the FT0002 oxygen index tester.

[0066] Weight gain rate: Place the samples before and after the combustion test in an oven at 100°C for 2 hours, place them in a dryer to dry, measure their weight after the weight of the sample is balanced, and calculate the weight gain rate; weight gain rate = (m1-m0) / m0×100%, where m0 is the weight of the sample before the test, and m1 is the weight of the sample after the test.

[0067] Test results: The test results of limiting oxygen index and weight gain rate are shown in Table 1.

[0068] Table 1 Limiting oxygen index and weight gain rate test results

[0069]

[0070] As shown in Table 1, the limiting oxygen index of the nylon fabric provided by the present invention can reach 29.4±0.1%, and the weight gain rate can reach 18.24%, which is significantly improved compared with the blank control group, and no molten droplets fall during combustion, and has a good flame retardant effect. Among them, the limiting oxygen index and weight gain rate of the nylon fabric prepared in Example 3 are the best, which is the best embodiment of the present invention.

[0071] Compared with Example 3, in step S4 of comparative example 1, aminopropyl triethoxysilane was not added, and in step S4 of comparative example 2, γ-glycidyloxypropyl trimethoxysilane was not added. However, the limiting oxygen index and weight gain rate of the obtained nylon fabric were significantly reduced compared with those of the blank control group, which indicates that the flame retardant effect of the co-polymerization of aminopropyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane in the present invention is better than that of the self-polymerization of aminopropyl triethoxysilane or the self-polymerization of γ-glycidyloxypropyl trimethoxysilane; in comparative example 3, the mixing mass ratio of γ-glycidyloxypropyl trimethoxysilane and aminopropyl triethoxysilane was changed, but the limiting oxygen index and weight gain rate of the obtained nylon fabric were reduced to varying degrees, which indicates that the flame retardant effect of the co-polymerization of γ-glycidyloxypropyl trimethoxysilane and aminopropyl triethoxysilane in the present invention is better than that of the self-polymerization of γ-glycidyloxypropyl trimethoxysilane. The dosage of triethoxysilane has been optimized. Changing its dosage can change the structure of the flame retardant on the surface of the nylon fabric, thereby affecting its flame retardant effect or affecting its grafting rate with the nylon fabric; Comparative Example 4 changes the dripping speed of the mixture of γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane, but the limiting oxygen index and weight gain rate of the prepared nylon fabric are significantly reduced, which shows that the dripping speed is the key to affecting the polymerization of γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane on the surface of the nylon fabric; Comparative Example 5 does not perform carboxylation modification on the nylon fabric, but the limiting oxygen index and weight gain rate of the prepared nylon fabric are significantly reduced, which shows that the carboxymethylation operation can increase the grafting rate of the flame retardant molecules on the nylon fabric, effectively improving the flame retardancy of the nylon fabric.

[0072] Test Example 2: Thermal Performance Test

[0073] Test samples: Nylon fabrics were prepared in Example 3 and Comparative Examples 1 to 5; blank samples were prepared using original nylon fabric.

[0074] Cone calorimetry test: According to ISO / DIS 13927-2001 "Simple heat release test for plastics using conical radiant heaters and thermopile detectors", the test size is 100mm×100mm, and the heat flux is 50kW / m 2 .

[0075] Test results: See the test results Figure 1 and Figure 2 .

[0076] Depend on Figure 1 It can be seen that the peak heat release rate of the nylon fabric in the blank control group is 456.9kW / m 2 The peak heat release rate of the nylon fabric prepared in Example 3 is 298.2 kW / m 2 Compared with the blank control group, the heat release rate of nylon fabric was significantly reduced. Figure 2It can be seen that the combustion heat peak of the nylon fabric prepared in Example 3 of the present invention is significantly shifted back, and the peak value is significantly reduced. In summary, the nylon fabric provided by the present invention has good flame retardancy.

[0077] The above embodiments are merely illustrative of the preparation method of the present invention, and are not intended to limit the present invention. Any person skilled in the art may not modify the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by a person of ordinary skill in the art without departing from the technical concept provided by the present invention are still covered by the claims of the present invention.

Claims

1. A method for preparing nylon fabric, characterized in that: The following steps are involved: S1. The nylon fabric was immersed in a sodium carbonate solution, heated to boiling and boiled for 1-2h, cooled, removed the nylon fabric, washed with water to obtain a pretreated nylon fabric; S2. The pretreated nylon fabric obtained in step S1 was immersed in an aqueous solution of ethylene glycol, tartaric acid was added, stirred at a speed of 1200-1400rpm for 0.5-1h, the nylon fabric was removed, washed with water to neutrality after drying, and dried at room temperature to obtain a modified nylon fabric I; S3. The modified nylon fabric I obtained in step S2 is immersed in a mixed solution of p-hydroxybenzoic acid and phosphate amide in ethanol, heated to 50-60 ° C, the immersion time is 1-1.5h, the nylon fabric is removed, and washed with water to obtain a modified nylon fabric II; S4. Soak the modified nylon fabric II obtained in step S3 in an aqueous solution of tetramethylphosphonium hydroxide and sodium dodecyl sulfate, heat to 40-50°C, dropwise add a mixture of γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane, stir for 3.5-4h, take out the nylon fabric, wash with clean water, and dry to obtain.

2. The method for preparing nylon fabric according to claim 1, characterized in that: The concentration of the sodium carbonate solution in step S1 is 0.06-0.08 mol / L, and the pH value is 8.5-9.

3. The method for preparing nylon fabric according to claim 1, characterized in that: The mass percentage of ethylene glycol in step S2 is 20-25%.

4. The method for preparing nylon fabric according to claim 1, characterized in that: The dosage of tartaric acid in step S2 is 15-17% of the mass of the nylon fabric.

5. The method for preparing nylon fabric according to claim 1, characterized in that: The immersion temperature in step S2 is 75-80°C.

6. The method for preparing nylon fabric according to claim 1, characterized in that: In step S3, the concentration of p-hydroxybenzoic acid is 0.5-0.7 mol / L, and the concentration of phosphate amide is 0.15-0.2 mol / L.

7. The method for preparing nylon fabric according to claim 1, characterized in that: In step S4, the concentration of tetramethylphosphonium hydroxide is 0.02-0.03 mol / L, and the concentration of sodium dodecyl sulfate is 0.03-0.04 mol / L.

8. The method for preparing nylon fabric according to claim 1, characterized in that: The dropping speed of the mixture of γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane in step S4 is 2.2-2.6m 3 / h.

9. The method for preparing nylon fabric according to claim 1, characterized in that: The mixing mass ratio of γ-glycidyloxypropyltrimethoxysilane and aminopropyltriethoxysilane in step S4 is 2-5:9-13.

10. A nylon fabric obtained according to the method for preparing nylon fabric according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Flame retardant graft modification method for nylon 66 fabric

    CN103866563A

  • Flame-retardant nylon and preparation method thereof

    CN116200027A

  • Surface-modified aramid fiber and preparation method thereof

    CN104404772A

  • Synthetic fiber / fabric inflaming retarding graft modified product and preparing method

    CN105484031A